ANALISIS KREATIVITAS ANAK USIA 5-6 TAHUN DALAM PEMBELAJARAN SENI TARI DI TK SANTO THOMAS 2 - Meysa Estevania Siregar; Elya Siska Anggraini (CV. ADIBA AISHA AMIRA, 2025)
This study is a qualitative study that aims to analyze the creativity of children aged 5-6 years in dance learning at TK Snto Thomas 2. The research method used is descriptive qualitative, with research subjects consisting of 2 children aged 5-6 years. The indicators studied include the ability to move in expressing imagination, the ability to move in mastering space, the ability to move in responding to sound/music. The findings of the study indicate that overall, the use of dance learning has a positive impact on children's creativity, especially on the ability to move in expressing imagination. This indicator is proven to have the most significant influence because through the dance learning that is carried out, children can train their imagination with dance movements according to the theme, story or atmosphere of the music. This process allows children to more easily express their imagination and creativity in dancing. In this dance activity, a conducive learning environment, varied teaching methods, and appropriate stimulation from teachers are the main factors that support the emergence of children's creativity. This study concludes that dance learning is very effective in increasing children's creativity, especially in dance learning.